Proteome profiling of flax (linum usitatissimum) seed: characterization of functional metabolic pathways operating during seed development - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Kadoo, Narendra Y.; Giri, Ashok P.; Gupta, Vidya S. (Journal of Proteome Research, 2012)
Flax (Linum usitatissimum L.) seeds are an important source of food and feed due to the presence of various health promoting compounds, making it a nutritionally and economically important plant. An in-depth analysis of the proteome of developing flax seed is expected to provide significant information with respect to the regulation and accumulation of such storage compounds. Therefore, a proteomic analysis of seven seed developmental stages (4, 8, 12, 16, 22, 30, and 48 days after anthesis) in a flax variety, NL-97 was carried out using a combination of ID-SDS-PAGE and LC-MSE methods. A total 1716 proteins were identified and their functional annotation revealed that a majority of them were involved in primary metabolism, protein destination, storage and energy. Three carbon assimilatory pathways appeared to operate in flax seeds. Reverse transcription quantitative PCR of selected 19 genes was carried out to understand their roles during seed development. Besides storage proteins, methionine synthase, RuBisCO and S-adenosylmethionine synthetase were highly expressed transcripts, highlighting their importance in flax seed development. Further, the identified proteins were mapped onto developmental seed specific expressed sequence tag (EST) libraries of flax to obtain transcriptional evidence and 81% of them had detectable expression at the mRNA level. This study provides new insights into the complex seed developmental processes operating in flax.
Keywords: alpha-linolenic acid; carbon flux; Digital expression analysis; flax seed development; MSE; secoisolariciresinol diglucoside